Obtenção e caracterização de produtos panificados livres de glúten - Schamne, Cristiane (2007)
The celiac disease is associated to food ingestion containing gluten, a protein that is found in some vegetable raw materials, as wheat, rye, barley and oats, damaging the surface of the intestine mucosa, making difficult nutrients absorption by the organism. The celiac disease has been object of frequent technological and clinical research on food alternatives to persons having the disease. The objective of this study was to develop the gluten free baked products, having a good sensorial acceptance, using cassava starch with the addition of soybeans derived products . From the rice cream, the cassava starch and the maize starch used in the formulation, the experimental design for Simplex-Centróide mixtures was carried through, and after that the software called Statistica 7.0 was used, inserting the maximum limit restriction of 50% of cassava starch, resulting in the experimental design for mixtures, giving then seven samples. Using these seven samples, sensorial and instrumental analysis composed of specific volume, elasticity and firmness analysis was carried through. For the sensorial analysis, the optimized formulation of mixture was 50% of rice cream and 50% of cassava starch, and for the instrumental analysis, the optimal simultaneous point for the three conducted analyses was 20% of rice cream, 50% of maize starch and 30% of cassava starch. From these two optimal points, a second sensorial analysis was realized, and the optimal formulation obtained from instrumental analyses was significantly preferred (hedonic scale average=6,96±1,71, using scale of 1 to 9) comparing to the first sensorial analysis (hedonic scale average=5,77±1,83, using scale of 1 to 9). From these samples, it was realized the comparative analysis of specific volume, elasticity, firmness and triangular test between baked bread and pre-baked and freeze bread. The baked sample and the pre-baked and freeze sample showed differences only in product elasticity, having not showed sensorial difference between the samples analyzed. For the muffin, a sensorial analysis was conducted, that resulted on hedonic scale average 7,76±1,07, using scale of 1 to 9. It was realized instrumental analysis of specific volume, elasticity and firmness, and comparative analysis between baked muffin and pre-baked and freeze muffin, adopting the same procedure used for bread analysis. The baked muffin and pre-baked and freeze muffin differed on specific volume and elasticity, however they didn´t have any sensorial difference when the triangular test was applied. For both, the bread and muffin, it was realized the physic-chemistry, nutritional and microbiological analysis, and both were according to the current law. It was realized cost analyses of the developed products, and the conclusion was that they are economically according with similar products.